1997
DOI: 10.1021/la970283h
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Adsorption onto Metal and Modified Interfaces:  Evidence for Adsorbate Penetration of an Alkanethiol Monolayer on Gold

Abstract: We have studied the adsorption of organic molecules from the vapor phase onto bare gold, n-octadecanethiol-modified, and 11-mercapto-1-undecanol-modified gold surfaces using a controlled atmosphere chamber with an ellipsometer and a quartz crystal microbalance for simultaneous in-situ determination of adsorbate thickness and mass. Our experimental data are fit by the BET adsorption isotherm, and results from these fits place limits on the ways in which the adsorbates can interact with the selected substrates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 71 publications
1
27
0
Order By: Relevance
“…Additional experiments carried out in a controlled atmosphere chamber indicate that full removal of the solvent molecules from the monolayer appears to be a rate‐limiting prerequisite for the onset of the ordering process. The presence of a limited number of intercalated solvent molecules in the disordered monolayer is supported by the electrochemical quartz balance and ellipsometric measurements reported by Blanchard and Karpovich 17 …”
mentioning
confidence: 67%
“…Additional experiments carried out in a controlled atmosphere chamber indicate that full removal of the solvent molecules from the monolayer appears to be a rate‐limiting prerequisite for the onset of the ordering process. The presence of a limited number of intercalated solvent molecules in the disordered monolayer is supported by the electrochemical quartz balance and ellipsometric measurements reported by Blanchard and Karpovich 17 …”
mentioning
confidence: 67%
“…We believe these discrepancies are related to solvent partitioning into the monolayer. It has been demonstrated that methanol and hexane measurably penetrate into even a close-packed alkanethiolate monolayer (56). SAMs of alkylsiloxanes lack the long-range order that SAMs of alkanethiolates possess (41)(42)(43)(44)(45)57), so penetration of the solvent is expected to be more significant in SAMs of alkylsiloxanes.…”
Section: Calculation Of the Work Of Adhesion With The Focg Modelmentioning
confidence: 99%
“…A value of n close to 1 may arise in either a) a constant rate of nucleation, combined with ordered domains of homogeneous size whose number increases with time, or b) an instantaneous (delta-shaped) nucleation rate, combined with a domain growth along one dimension only. [17] Our results provide for the first time evidence of the dynamic structure of alkanethiol SAMs in contact with a liquid phase. [16] As shown in the inset of Figure 3, peak widths remain constant during the ordering process, thus providing a time-independent average mosaic size of 50 nm.…”
Section: Methodsmentioning
confidence: 71%